A new genus of oryzomyine rodents (Cricetidae, Sigmodontinae) with three new species from montane cloud forests, western Andean cordillera of Colombia and Ecuador - Brito, Jorge (2020)
The Andean cloud forests of western Colombia and Ecuador are home to several endemic mammals; members of the Oryzomyini, the largest Sigmodontinae tribe, are extensively represented in the region. However, our knowledge about this diversity is still incomplete, as evidenced by several new taxa that have been described in recent years. Extensive field work in two protected areas enclosing remnants of Chocó montane forest recovered a high diversity of small mammals. Among them, a medium-sized oryzomyine is here described as a new genus having at least three new species, two of them are named and diagnosed. Although externally similar to members of the genera Nephelomys and Tanyuromys, the new genus has a unique molar pattern within the tribe, being characterized by a noticeable degree of hypsodonty, simplification, lamination, and third molar compression. A phylogeny based on a combination of molecular markers, including nuclear and mitochondrial genes, and morphological data recovered the new genus as sister to Mindomys, and sequentially to Nephelomys. The new genus seems to be another example of a sigmodontine rodent unique to the Chocó biogeographic region. Its type species inhabits cloud forest between 1,600 and 2,300 m in northernmost Ecuador (Carchi Province); a second species is restricted to lower montane forest, 1,200 m, in northern Ecuador (Imbabura Province); a third putative species, here highlighted exclusively by molecular evidence from one immature specimen, is recorded in the montane forest of Reserva Otonga, northern Ecuador (Cotopaxi Province). Finally, the new genus is also recorded in southernmost Colombia (Nariño Department), probably represented there also by a new species. These species are spatially separated by deep river canyons through Andean forests, resulting in marked environmental discontinuities. Unfortunately, Colombian and Ecuadorian Pacific cloud forests are under rapid anthropic transformation. Although the populations of the type species are moderately abundant and occur in protected areas, the other two persist in threatened forest fragments.